IMPACT OF SOCIAL MEDIA ON MENTAL HEALTH (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Drawing on insights from The Anxious Generation by Jonathan Haidt, this article explores the growing impact of social media on adolescent mental health. In recent years, there has been a notable rise in anxiety, depression, and emotional distress among young people, coinciding with the widespread adoption of smartphones and social media platforms.The objective of this article is to examine how increased screen exposure and online interaction contribute to these mental health challenges. Key factors discussed include the shift from a play-based to a phone-based childhood, leading to reduced real-world socialization, increased social comparison, and disrupted sleep patterns. Additionally, the article highlights mechanisms such as algorithm-driven engagement, validation-seeking behavior, and the psychological effects of constant online connectivity. These elements are analyzed in relation to their role in intensifying emotional vulnerability, particularly among adolescents.